Boosting NiFe-LDH by ruthenium dioxide for effective overall water splitting. (19th March 2023) - Chen, Qingrong; Kang, Zhenye; Luo, Shengxu; Li, Jing; Deng, Peiling; Wang, Chongtai; Hua, Yingjie; Zhong, Shengkui; Tian, Xinlong
Abstract: Rational design of efficient electrocatalysts for water electrolysis is very important for realizing the industrial hydrogen production. Here, a RuO2 -modified NiFe-LDH catalyst (RuO2 /NiFe-LDH/NF) was designed and synthesized for driving the water splitting, combining the advantages of both RuO2 and LDHs. For oxygen evolution and hydrogen evolution reactions, RuO2 /NiFe-LDH/NF needs an overpotential of 99 and 226 mV, respectively, to reach 10 mA cm −2 . More importantly, RuO2 /NiFe-LDH/NF shows a voltage of 1.52 V toward water electrolysis at 10 mA cm −2, which is much lower than that of the RuO2 ||Pt/C pair (1.64 V). Moreover, the RuO2 /NiFe-LDH/NF catalyst demonstrates an excellent durability with negligible potential variation after more than 100 h stability test. This work shows that the integration of RuO2 and NiFe-LDH is a promising strategy for synthesizing robust catalyst for water electrolysis. Graphical abstract: Image 1 Highlights: Nanocomposite RuO2 /NiFe-LDH/NF was prepared by a facile hydrothermal procedure. RuO2 /NiFe-LDH/NF showed well performance with a cell voltage of 1.52 V. The strong interaction between NiFe-LDH and RuO2 plays an important role.